Bidimensional unconstrained optimization approach to EMD: An algorithm revealing skin perfusion alterations in pseudoxanthoma elasticum patients. (March 2017) - Humeau-Heurtier, Anne; Colominas, Marcelo A.; Schlotthauer, Gastón; Etienne, Maxime; Martin, Ludovic; Abraham, Pierre
Highlights: PXE is an inherited and systemic metabolic disorder that primarily affects skin. We study skin microvascular flow (LSCI data) of PXE and control healthy subjects. LSCI data are studied with 2D-UOA-EMD. We reveal spatial patterns on local textures. These spatial patterns are different in PXE patients and in control subjects. For the first time, microvascular perfusion alterations in PXE subjects are shown. Abstract: Background and Objective: Pseudoxanthoma elasticum (PXE) is an inherited and systemic metabolic disorder that affects the skin, leading among other things to a peau d'orange appearance. Unfortunately, PXE is still poorly understood and there is no existing therapy to treat the disease. Because the skin is the first organ to be affected in PXE, we propose herein a study of skin microvascular perfusion. By means of this analysis, our goal is to increase knowledge of PXE.Methods: For this purpose, microvascular data from patients suffering from PXE and from healthy control subjects were recorded using the laser speckle contrast imaging (LSCI) modality. These data were processed using the recent 2D version of the unconstrained optimization approach to empirical mode decomposition (UOA-EMD). Our work therefore corresponds to the first time this algorithm has been applied to biomedical data.Results: Our study shows that the 2D-UOA-EMD is able to reveal spatial patterns on local textures of LSCI data. Moreover, these spatial patterns differ between PXE patients and control subjects. Quantification measure of these spatial patterns reveals statistical significant differences between PXE and control subjects, in the neck ( p = 0.0004 ) and in the back ( p = 0.0052 ).Conclusions: For the first time, alterations in microvascular perfusion in PXE patients have been revealed. Our findings open new avenues for our understanding of pathophysiologic skin changes in PXE.